From the Baldwin primer to the Monroe survey a short history of public elementary school textbooks, 1901-1932 - van-Heugten, Ma. Lina Nepomuceno (2002)
Much has been made of how poorly adapted to Philippine conditions were the first schoolbooks used by Filipino children. The American teachers even at the time were all in agreement that the books dealt with things that were unfamiliar to the Filipino child. Efforts to find a solution to this nagging problem could only be described as persistent and determined. Consequently, textbooks were constantly being changed. Given this information. one may be led to believe that the choice of textbooks would have been markedly altered by a succession of top education administration officials. Fred Atkinson, David Barrows, and Frank White. But apropos of this, perhaps there may be some truth, after all, in the saying that "the more things change, the more they remain the same," relative to the textbook situation obtaining during the period covered by this study. For, despite the heroic efforts exerted by all parties concerned, the same observations made about the textbooks in 1901 were again made by the Philippine Islands Board of Educational Survey composed of Dr. Paul Monroe. Dr. Stephen P. Daggman, and Mr. Jose Perez twenty four years later. This paper seeks to provide a short history of the evolution of textbooks used in Philippine elementary schools from 1901-1932, and to provide a preliminary assessment of how recommendations made by the Monroe Survey of 1925 made an impact on subsequent textbook choices for Philippine elementary schools.